PENINGKATAN KADAR PATCHOULI ALCOHOL PADA MINYAK NILAM (Pogostemon cablin Benth) DENGAN METODE DISTILASI FRAKSINASI VAKUM - Rahma Isfaroiny; Mitarlis (The East Java Biological Society, 2005)
The quality of nilam (Pogostemon cablin Benth) oil depend on it patchouli alcohol value. At there time nilam farmers just has produced nilam oil with patchouli alcohol value about 26–28%. To increase this value, fractional vacuum distillation had been done in this study. Nilam oil has been isolated from drying leaf of nilam plant. Patchouli alcohol in this oil was analyzed by gas chromatography, next the oil was distillated by fractional vacuum and the patchouli alcohol was determined from each fraction. This study showed that fractional vacuum distillation of nilam oil gives a higher patchouli alcohol value. The increasing was 23.3387%; from 35.022% at nilam oil before fractination vacuum distillation to 58.3515% at the third fraction from fractional vacuum distillation. In fact, the fourth fraction had the highest patchouli alcohol, but it had dark colour so isn’t fill the standard quality.